Centrosome amplification and cancer: A question of sufficiency. - Raff, J; Basto, R (Elsevier, 2017)
Centrosome amplification is a common feature of many types of cancer, but whether it is a cause or consequence is hotly debated. In this issue of Developmental Cell, Levine et al. (2017) provide strong evidence that centrosome amplification is sufficient to initiate tumorigenesis in a mouse model.